2005
DOI: 10.1245/aso.2005.11.024
|View full text |Cite
|
Sign up to set email alerts
|

The Second International Conference on Sentinel Node Biopsy in Mucosal Head and Neck Cancer

Abstract: The conference attracted delegates from all over the world, thus underscoring the high interest in the topic. With regard to the presented data and the data from the literature, SNB for early oral and oropharyngeal cancer is sufficiently validated. The consensus conference resulted in the definition of minimal methodological requirements for accurate SNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 23 publications
(27 reference statements)
3
86
0
3
Order By: Relevance
“…Identification of SLN is done by radio colloid alone, blue dye alone or combination of both radio colloid and blue dye. Studies have shown identification rate of 97 % (range 90-100 %), negative predictive value of 96 % (range 88-100 %) [5]. There are very limited studies where they have used only blue dye to identify SLN.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of SLN is done by radio colloid alone, blue dye alone or combination of both radio colloid and blue dye. Studies have shown identification rate of 97 % (range 90-100 %), negative predictive value of 96 % (range 88-100 %) [5]. There are very limited studies where they have used only blue dye to identify SLN.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify a potential prognostic relevance for occult metastasis of SOX2 protein expression, we consequently analysed a very well defined patient cohort with early oral SCC (T1/T2-stage) undergoing sentinel lymph node biopsy. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…; ipsilateral). Here it is shown to be quite sensitive at 97% on average (range: 96-100%); however, there is still a small false negative rate (average 4%, range: 0-12%) [18][19][20]. Potential explanations for this are skip metastases and 'masking' of a sentinel node by adjacent radiotracer uptake from carcinomas of the floor of mouth particularly in level I.…”
Section: Sentinel Nodesmentioning
confidence: 80%
“…Nonetheless, it is currently used in lieu of elective neck dissection in select cases at several institutions. The recommended indications for SLNB as proposed by 'The Second International Conference on Sentinel Node Biopsy in Mucosal Head and Neck Cancer' [18] are as follows: (1) staging of the ipsilateral neck in unilateral cT1/2 cN0 tumors, (2) staging of the ipsilateral and contralateral neck in midline tumors or tumors crossing the midline (cT1/2 cN0), and (3) staging of the contralateral neck in midline tumors or tumors crossing the midline (cT1/2 cN? ; ipsilateral).…”
Section: Sentinel Nodesmentioning
confidence: 99%